Economies of Scale: Some Statistical Evidence: Reply - Moore, Frederick T. (Quarterly Journal of Economics, 1960)
Journal Article Economies of Scale: Some Statistical Evidence: Reply Get access Frederick T. Moore Frederick T. Moore The RAND Corporation, Washington, D.C. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 74, Issue 3, August 1960, Pages 497–499, https://doi.org/10.2307/1883064 Published: 01 August 1960